PERSEPSI MAHASISWA MENGENAI PROMOSI CASHBACK DAN LAYANAN PAYLATER DALAM MEMBENTUK POLA KONSUMSI - Alisa Hidayatun Nafi’ah; Ayu Widia Wulandari; Cahya Fitryningtyas; Debby Mardhatillah; Dian Fatimah; Dita Aisyah; Dwivo Monica Risqi Putri; Lutfiyah Qilfa Khairil Aini; Risma Wardani (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
This study examines students' perceptions of cashback promotions and PayLater services and their impact on consumption patterns. The method used is qualitative with a phenomenological approach through in-depth interviews with students who use PayLater services. The results show that cashback promotions and the convenience of PayLater encourage consumptive behavior, where students tend to shop more frequently and purchase items that are not necessarily needed. Cashback is seen as an incentive that increases shopping frequency, while PayLater creates the illusion of additional funds, making credit purchases easier. This situation poses potential financial risks, such as debt accumulation. The study emphasizes the importance of financial literacy education to help students manage the use of digital financial services wisely.